Patients' experience of identifying and managing exacerbations in COPD: a qualitative study - Williams, V; Hardinge, M; Ryan, S; Farmer, A (Nature Publishing Group, 2014)
Effective self-management in chronic obstructive pulmonary disease (COPD) is crucial to reduce hospital admissions and improve outcomes for patients. This includes early detection and treatment of exacerbations by patients themselves.To explore patients' current understanding and experience of managing and identifying COPD exacerbations at home.A qualitative, interview-based study was carried out in patients' homes. Interviews were audio-recorded, transcribed and analysed using a grounded theory approach. Forty-four patients (17 women, 27 men; age range 55-85 years), with moderate-to-very-severe COPD, were recruited to the interview study from primary and secondary care settings in Oxford, UK, during 2012-2013.Patients identified exacerbations on the basis of measurable, 'visible' symptoms, such as cough and sputum and 'invisible' symptoms, such as chest sensations and bodily knowledge. Most patients seemed to use a combination of these approaches when identifying exacerbations, according to the symptoms that had the most impact on their well-being. Patients used additional self-management strategies during an exacerbation, such as self-medication (antibiotics and steroids) and monitored their recovery. Contact with health-care professionals usually occurred when patients felt no longer able to manage themselves.Patients use both assessment of objective biomarkers, which are aligned with medical knowledge, and subjective symptoms based on their experience, to identify and manage exacerbations of COPD. Health-care professionals and clinicians should acknowledge this 'expert patient' knowledge and integrate this into patients' care plans to facilitate early recognition and treatment of exacerbations.